Determining of death: the laws in force and future prospects - Fiori, Angelo; Di Pietro, Maria Luisa (Medicina e Morale, 1993)
Among the reasons for the delay of the approvai in Italian Parliament of he Law by decree (DDl.) n. 3280/1988 regarding organ transplantation, was the difficulty in reaching an agreement about the definition of the criteria for detennining death, a difficulty that was also caused by the need to not subordinate this diagnostic act to the sole purpose of withdrawing organs ex-cadavere. This is why the present legislative tendency is to separate the problem of determining death from that of transplanting organs, thus indicating single criteria even in the face of different requirements (e.g. whether or not to use life sustaining therapy). For this reason some DDLS (n. 4613(1990; n. 3280/1990; n. 764-A/1993) were presented during the X and XI Legislature. The Authors of this article have studied the contents of these DDLS and have compared them to the laws in force in other countries. This analysis is preceded by a historical excursus on the evolution of the Italian laws regarding detennining death (from Royal Decree n. 448/1892 to Ministerial Decree 9/1 /1970) and by a description of the contents of the present law.